Pathological lesions of kidney in experimentally infected mice with Toxoplasma gondii isolated from placenta of goats and ewes - Entissar Kanani; Ridha Hammo; Nabeel alneaymi (College of Education for Pure Sciences, 2010)
ABSTRACT This study was conducted to follow up the histopathological changes in kidney of mice experimentally infected with tissue cysts of Toxoplasma gondii, isolated from placenta of women, ewes, and does naturally infected at 3-120 days via inoculation 1 ml suspension intraperitoneally (i.p). Results of this study showed presence of pathological lesions from the third day up to 120 days post infection depending on period of infection. In kidney cortex pathological lesions were characterized by vacuolar degeneration in epithelial lining of convoluted tubules associated with acute cell swelling, congestion of blood vessels accompanied with the presence of focal area of coagulative necrosis mixed with tachyzoites, infiltration of mononuclear inflammatory cells (lymphocytes), also invasion of tachyzoites into epithelial cell lining tubules has been seen. Hypertrophy of glomerula has been seen, dilation of bowman spaces, congestion of capillaries in glomerular tuft as well as accumulation of tachyzoites, and infiltration of inflammatory with lymphocytes in and around the glomerula, also has been seen. Tissue cysts appeared at 7 days post infection in kidney of mice infected with does isolates, while tissue cysts appears after 14 days post infection in kidneys of mice infected with women and ewes isolates. Histopathological lesion that mentioned above observed in kidney of mice infected with does isolate was more intensive, concomitant, with pelvis arteriosclerosis invasion of tachyzoites into arterial wall, granulomatous lesion appeared in nephron tissue of kidney 40-120 days post infection.